KETIKA KOMPETENSI AUDITOR BERTEMU REPUTASI AUDITOR: ANALISIS MEDIASI TERHADAP BIAYA AUDIT - Destin Alfianika Maharani; Heni Purwantini (UNPERBA, 2026)
This study aims to examine the effect of auditor competence on audit fees with auditor reputation as a mediating variable in companies included in the SRI-KEHATI Index. The study employs a quantitative approach using secondary data obtained from companies’ annual reports and sustainability reports. The sample is selected using purposive sampling based on data availability and relevance. Hypotheses are tested using regression analysis and mediation analysis to identify both direct and indirect effects among variables. The results show that auditor competence does not have a direct effect on either auditor reputation or audit fees, while auditor reputation has a positive effect on audit fees. These findings indicate that the audit market does not directly price auditor competence when determining audit fees, but instead relies on auditor reputation as a quality signal. Furthermore, auditor reputation is found to fully mediate the relationship between auditor competence and audit fees, suggesting that auditor competence has economic implications only when it is recognized by the market and reflected in auditor reputation. This study supports Agency Theory and the Economics of Auditing Theory, which emphasize that the audit market relies on observable signals such as auditor reputation to assess audit quality and determine audit pricing. This study contributes to the literature by filling the research gap on the mechanism through which auditor competence is translated into audit fees, particularly in the context of emerging markets.